Quality of Population Administration Services at Pangkajene Village, Maritengngae District Sidenreng Rappang Regency - Muh. Fadlan; Andi Cudai Nur; Haedar Akib (Universitas Negeri Makassar, 2022)
This study aims to determine the Quality of Population Administration Services in Pangkajene Village, Maritengngae District, Sidenreng Rappang Regency in the process of making a cover letter for making an ID card as measured by indicators Tangible, Reliable, Responsiveness, Competence, Courtesy, Credibility, Security, Access, Communication, Understanding The Customer. This type of research is descriptive qualitative with data collection techniques were carried out by means of observation, interviews, and documentation. The validity of the data is checked through triangulation. The data analysis technique used data reduction, data presentation, and drawing conclusions. The results of this study indicate that all the dimensions used to measure the Quality of Population Administration Services in Pangkajene Village, Maritengngae District, Sidenreng Rappang Regency, have almost run optimally, it takes a high concentration in providing services in this case population administration, so the people are satisfied with the services provided.